THE INFLUENCE OF CUCUMBER JUICE (Cucumis Sativus Linn) ON BLOOD PRESSURE REDUCTION IN HYPERTENSION PATIENTS AT SINDANG BARANG BOGOR: PENGARUH PEMBERIAN JUS MENTIMUN (Cucumis Sativus Linn) TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI KELURAHAN SINDANG BARANG KOTA BOGOR - Sariaman Sariaman Purba (Wijaya Husada, 2019)
Introduction:In 2015 based on the WHO (World Health Organization) recorded it almost 1 billion people around the world have high blood pressure. Hypertension is one of the main causes of early mortality around the world. In 2020 around 1.56 billion adults will live with hypertension. Prevalence of hypertension for the population aged between 18 years and over in 2007 was 31.7% this is based on the results of blood pressure measurement of Riskesdas (Basic Health Research) in Indonesia 2013. Meanwhile, if we compared to 2013 there was a decrease as much as 5.9% (from 31.7% to 25.8%). In 2013 Riskesdas also recorded the incidence of hypertension in West Java was 13,612,359 people or 29.4%. Hypertension becomes the first sequence of disease outpatient on elderly patients throughout Puskesmas Bogor City with 99.260 (14,18%) cases. Purpose: This study aims to find out the effect of cucumber juice (cucumis sativus linn) towards the reduction of blood pressure for hypertension patients in Sindang Barang village of Bogor City. Methods:The type of this research is an experiment with quasy experimental design and non randomized pretest posttest control group. The population in this studies are all of the hypertension patients in Sindang Barang village of Bogor City, with 20 samples researched that using total sampling technique, and the retrieval to complete the material information were used interview techniques at the preliminary studied and observation sheet when the research was begin. Result:There is shown the differences result of the blood pressure before and after intervention group as 0.000 (P <0.05), and the differences in the results of the blood pressure before and after the control group as 0,564 (P> 0.05), and there were differences in the results of the blood pressure between the intervention group and the control group as 0.000 (P <0.05). Conclusion :There is an effect cucumber juice (cucumis sativus linn) towards the reduction of blood pressure for hypertension patients in Sindang Barang village of Bogor City. The results of this research might become knowledge for postoperative patients to reduce blood pressure by combining medical and non-treatment medical.